109 Multimodal Endovascular Endoscopy in Carotid Atherosclerotic Disease. (1st August 2016) - Savastano, Luis E.; Smith, Arlene; Vega, Karla; Murga-Zamalloa, Carlos; Gordon, David; Wang, Micheal; Thompson, B. Gregory; Seibel, Eric; Wang, Thomas
Abstract: INTRODUCTION: Disruption of vulnerable atherosclerotic plaque is the precipitating factor that culminates in thrombosis and ischemia. Current technologies do not have sufficient power to identify subtle thrombogenic lesions (ie, ulcers) in the arterial endoluminal surfaces nor reliably predict markers for future symptomatology. We developed an ultra-thin scanning fiber endoscope (SFE) to directly visualize the endoluminal surface of carotid arteries and identify structural, chemical, and biological markers of vulnerable and complicated atherosclerotic plaques. METHODS: 1.2 mm and 2.1 mm endoscopes containing single optical fiber scanned by a piezoelectric drive mechanism were developed to illuminate tissue surfaces with red, blue, and green laser beams (RBG). Laser-induced backscattering (reflectance) and tissue fluorescence collected by a ring of optical fibers were then digitalized to reconstruct color videos with large fields of view. Then, SFE was studied ex vivo in human carotid arteries and in vivo in a rabbit model of atherosclerosis. After imaging, specimens were processed for histology; lesions were independently reviewed by 2 pathologists and matched to endoscopic images with analysis of variance. RESULTS: High-definition structural and chemical images of 20 carotid arteries harvested during hospital autopsies revealed 42 lesions. Based on anatomical features and tissue fluorescence, we developed a classifier that enabled identification of: healthy endovascular regions (smooth surfaces with strong homogeneous fluorescence); early plaques (dot or streak-like elevated lesions with low fluorescence); advance plaques (irregular elevated lesions with minimal to absent fluorescence); and complicated plaques (ulcers: punch-out dark-gray lesions with raised irregular bead-like borders and speckled fluorescence pattern; hematoma: absent reflection, black regions, and fluorescence). The image quality and validity of the classifier were reproduced in vivo in an atherogenic rabbit model. CONCLUSION: Multimodal SFE generates high-definition structural and label-free chemical images, and detects with high sensitivity and specificity small intravascular thrombi and subtle surface thrombogenic lesions in nonstenosing complicated plaques, even in cases not detected by conventional diagnostic modalities. Therefore, it holds the potential for becoming a new imaging platform in cerebrovascular and cardiovascular disease.